Answer:
185
Step-by-step explanation:
sorry. had to do something but im bsck :)
Home to 1st base = 90 ft
1st base to 2nd base = 90 ft
2nd base to 3rd base = 90 ft
3rd base to home = 90 ft
so we have a total of : (90 * 4) = 360 ft
there are 3 ft in 1 yd....
so in 360 ft, there are : 360/3 = 120 yds <==
or u could just figure it between each base....90 ft = (90/3) = 30 yds per base...and u have 4 bases....so that (4 * 30) = 120 yds
Step-by-step explanation:
s ks ok w merto s mak osmwokwmsos
G^2-4g+6
# Terms: 3, (g^2), (-4g), (6)
Variable: g
Constant: 6